Electronic Prescribing and HIPAA Privacy Regulation - Michael D. Greenberg; M. Susan Ridgely; Douglas S. Bell (SAGE Publishing, 2004)
Electronic prescribing offers the prospect of safer medication management, but fulfillment of that promise depends on ready access to personal health information from many sources, thus raising new concerns about information privacy and security. Federal privacy regulations under the Health Insurance Portability and Accountability Act of 1996 (HIPAA) limit the sharing of health information by providers, and particularly may discourage information sharing over distributed computer networks. This analysis finds that although HIPAA has only a limited effect on current e-prescribing practices, future electronic prescribing systems will likely fall short of their potential benefits, absent policy refinements designed to encourage clinically appropriate, networked sharing of patient health information.